Adaptation of cardiomyogenesis to the generation and maturation of cardiomyocytes from human pluripotent stem cells. Issue 1 (8th November 2022) - Martyniak, Alicja; Jeż, Mateusz; Dulak, Józef; Stępniewski, Jacek
Abstract: The advent of methods for efficient generation and cardiac differentiation of pluripotent stem cells opened new avenues for disease modelling, drug testing, and cell therapies of the heart. However, cardiomyocytes (CM) obtained from such cells demonstrate an immature, foetal‐like phenotype that involves spontaneous contractions, irregular morphology, expression of embryonic isoforms of sarcomere components, and low level of ion channels. These and other features may affect cellular response to putative therapeutic compounds and the efficient integration into the host myocardium after in vivo delivery. Therefore, novel strategies to increase the maturity of pluripotent stem cell‐derived CM are of utmost importance. Several approaches have already been developed relying on molecular changes that occur during foetal and postnatal maturation of the heart, its electromechanical activity, and the cellular composition. As a better understanding of these determinants may facilitate the generation of efficient protocols for in vitro acquisition of an adult‐like phenotype by immature CM, this review summarizes the most important molecular factors that govern CM during embryonic development, postnatal changes that trigger heart maturation, as well as protocols that are currently used to generate mature pluripotent stem cell‐derived cardiomyocytes.